Keagenan Bank dalam Perspektif Common Law System - Andika Persada Putera (Perspektif Hukum, 2016)
The rapid development of the national economy and banking external environment, causing banking activities not only engage in activities that are primary (core business), but also non-core business such as agency activities as Mutual Fund Sales Agent (APERD) and Bancassurance. In the concept of the common law system, the agency as the center of all business affairs as a business owner can not do your own business, so delegating affairs to agents as a mediator. There is a legal relationships and trust (fiduciary relationship) between the principal and the agent acting on behalf principal. In addition, there is an element of supervision of the principal to the agent so that the agent must comply under the supervision of the principal. Supervision is an essential element that determines the existence of an agency relationship, so it is a vertical relationship between principal and agent. The principal control components in the form of action directives, orders, limitation of power agents and monitoring the agent's action